2019
DOI: 10.1155/2019/5341281
|View full text |Cite
|
Sign up to set email alerts
|

Pylephlebitis: A Case of Inferior Mesenteric Vein Thrombophlebitis in a Patient with Acute Sigmoid Diverticulitis—A Case Report and Clinical Management Review

Abstract: Pylephlebitis is a rare complication of intra-abdominal infections and describes thrombosis and infection as two different pathophysiological phenomena in the cause of this disease. The nonspecific presentation of disease makes its diagnosis difficult and thus leads to high mortality. The treatment comprises antibiotics and also includes controversial use of anticoagulation in these patients. Here, we present a patient with past medical history of human immunodeficiency virus and past diverticulitis who presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
8
0
2
Order By: Relevance
“…In a case report by Sherigar et al it was concluded that the indication for thrombolytic therapy was similar to that of using anticoagulation, that is, it can be used to prevent the progression of the thrombus and be used if a patient shows signs of portal hypertension, which is a complication associated with higher mortality [15]. At this time, there are no clinical trials that have commented on anticoagulation duration or have compared the efficacy of different types of anticoagulation regimens in patients with pylephlebitis [16]. Historically, patients have been treated with heparin, low molecular weight heparin, warfarin, and novel oral anticoagulants (NOACs), with a recent increase in the use of NOACs [16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a case report by Sherigar et al it was concluded that the indication for thrombolytic therapy was similar to that of using anticoagulation, that is, it can be used to prevent the progression of the thrombus and be used if a patient shows signs of portal hypertension, which is a complication associated with higher mortality [15]. At this time, there are no clinical trials that have commented on anticoagulation duration or have compared the efficacy of different types of anticoagulation regimens in patients with pylephlebitis [16]. Historically, patients have been treated with heparin, low molecular weight heparin, warfarin, and novel oral anticoagulants (NOACs), with a recent increase in the use of NOACs [16][17].…”
Section: Discussionmentioning
confidence: 99%
“…At this time, there are no clinical trials that have commented on anticoagulation duration or have compared the efficacy of different types of anticoagulation regimens in patients with pylephlebitis [16]. Historically, patients have been treated with heparin, low molecular weight heparin, warfarin, and novel oral anticoagulants (NOACs), with a recent increase in the use of NOACs [16][17].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] A TC na fase venosa portal é o meio complementar mais sensível, mas o diagnóstico final pode ser estabelecido através de ecografia com doppler ou TC com contraste, como no caso apresentado. [7][8][9] Uma vez estabelecido o diagnóstico e identificada a causa da tromboflebite, o tratamento deve ser iniciado de imediato com antibioterapia de largo espectro e hipocoagulação. 8,9 A antibioterapia constitui o principal tratamento para a pileflebite, sendo necessário início empírico para as bactérias mais comuns (Bacteroides fragilis, Escherichia coli e anaeróbios), devendo-se ajustar o antibiótico de acordo com o resultado cultural.…”
Section: Discussionunclassified
“…[7][8][9] Uma vez estabelecido o diagnóstico e identificada a causa da tromboflebite, o tratamento deve ser iniciado de imediato com antibioterapia de largo espectro e hipocoagulação. 8,9 A antibioterapia constitui o principal tratamento para a pileflebite, sendo necessário início empírico para as bactérias mais comuns (Bacteroides fragilis, Escherichia coli e anaeróbios), devendo-se ajustar o antibiótico de acordo com o resultado cultural. Alguns autores defendem que a duração do tratamento deve ser de 4 a 6 semanas, sendo 2 a 3 semanas de antibiótico endovenoso.…”
Section: Discussionunclassified
“…Bacteroides specifically increases thrombosis through production of anticardiolipin antibodies which breakdown heparin and the presence of capsular components which accelerate fibrin cross-linking [8,9] . Regardless of bacteraemia or culture isolates, broad spectrum antibiotic therapy is recommended in the literature [10] we used intravenous piperacillin/tazobactam 4g/0.5g four times a day.…”
Section: Case Reportmentioning
confidence: 99%